Cochrane Database of Systematic Reviews 2009
DOI: 10.1002/14651858.cd007899
|View full text |Cite
|
Sign up to set email alerts
|

Paying for performance to improve the delivery of health interventions in low and middle-income countries 

Abstract: Paying for performance to improve the delivery of health interventions in low-and middle-income countries (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
145
0
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(156 citation statements)
references
References 6 publications
3
145
0
6
Order By: Relevance
“…3 See Witter et al (2011) for a recent systematic review of health care performance incentives in low-and middleincome countries. Most of the literature that they cite do not have control groups and estimate the impact of P4P as jumps in time trends of the amount of services providers by treatment facilities.…”
mentioning
confidence: 99%
“…3 See Witter et al (2011) for a recent systematic review of health care performance incentives in low-and middleincome countries. Most of the literature that they cite do not have control groups and estimate the impact of P4P as jumps in time trends of the amount of services providers by treatment facilities.…”
mentioning
confidence: 99%
“…In a recent Bulletin editorial, for example, Fretheim et al reported the results of their Cochrane review of performance-based financing studies, which yielded few studies meeting Cochrane criteria. When the authors concluded that little could be said about performance-based financing, 4,5 advocates of this approach responded with an avalanche of critical commentaries. 6 These debates are typical, necessary and energizing.…”
mentioning
confidence: 99%
“…For hospitals, prevalent mechanisms include global budgets, capitation payments, fees for service and payment based on diagnosisrelated groups (DRG). In addition, performance-and results-based financing is increasingly being explored and evaluated, and may be useful in certain contexts (Langenbrunner et al 2009;Lagarde et al 2010;Witter et al 2012). Each mechanism has its strengths and weaknesses.…”
Section: Shared Responsibilities For Healthmentioning
confidence: 99%